Zinc supplementation in rats subjected to acute swimming exercise: Its effect on testosterone levels and relation with lactate - Kaya, Oktay; Gokdemir, Kadir; Kilic, Mehmet; Baltaci, Abdulkerim Kasim (Maghira & Maas Publications, 2006)
OBJECTIVE: There is fairly scarce information about the effects of zinc, an essential trace element, on performance. Studies concerned with the relation between zinc and exercise mostly concentrate on the distribution of this element in the body in response to exercise. The objective of the present study is to explore how zinc supplementation affects testosterone levels and its relation with lactate in rats subjected to acute swimming exercise. MATERIALS AND METHODS: Thirty adult male rats of Spraque-Dawley species were equally allocated to 3 groups. Group 1: Control. Group 2: Group subjected to 30-minute acute swimming exercise. Group 3: Group supplemented with intraperitoneal (i.p.) zinc (3mg/kgday) for 4 weeks and subjected to 30-minute swimming exercise. Blood samples collected from all experimental animals by decapitation method were analyzed to determine free and total testosterone and lactate levels in the plasma. RESULTS: Group 3 had the highest free and total testosterone levels, followed by Group 1 and Group 2. The highest lactate levels were found in Group 2 and the levels in Group 3 were higher than those in Group 1. CONCLUSION: Results of the study demonstrate that zinc supplementation leads to a significant increase in testosterone levels and a significant decrease in lactate levels. In conclusion, physiological doses of zinc supplementation can be useful for performance.
Keywords: zinc supplementation; exercise; testosterone; lactate